What could you do with 400 years of biological history on african americans? Evaluating the potential scientific benefit of systematic studies of dental and skeletal materials on African Americans from the 17th through 20th centuries. Issue 4 (9th January 2016) - Jackson, Fatimah; Jackson, Latifa; Cross, Christopher; Clarke, Cameron
Abstract : Objectives: How important is it to be able to reconstruct the lives of a highly diverse, historically recent macroethnic group over the course of 400 years? How many insights into human evolutionary biology and disease susceptibilities could be gained, even with this relatively recent window into the past? In this article, we explore the potential ramifications of a newly constructed dataset of Four Centuries of African American Biological Variation (4Cs). Methods: This article provides initial lists of digitized variables formatted as SQL tables for the 17th and 18th century samples and for the 19th and 20th century samples. Results: This database is dynamic and new information is added yearly. The database provides novel opportunities for significant insights into the past biological history of this group and three case study applications are detailed for comparative computational systems biology studies of (1) hypertension, (2) the oral microbiome, and (3) mental health disorders. Conclusions: The 4Cs dataset is ideal for interdisciplinary "next generation" science research and these data represent a unique step toward the accumulation of historically contextualized Big Data on an underrepresented group known to have experienced differential survival over time. Am. J. Hum. Biol. 28:510–513, 2016. © 2016 The Authors American Journal of Human Biology Published byWiley Periodicals, Inc.